A STUDY TO ASSESS THE TFFECTIVENESS OF PLANNED TEACHING PROGRAMME (PTP) ON POLYCYSTIC OVARIAN SYNDROME (PCOS) AMONG ADOLESCENT GIRLS IN SELECTED HIGH SCHOOLS AT MANGALORE - D'Souza, Pramila (Journal of Health and Allied Sciences NU, 2013)
A study was done to assess the effectiveness of planned teaching programme (PTP) on polycystic ovarian syndrome (PCOS) among adolescent girls in selected high schools at Mangalore. The main objectives of the study were1. To assess the pre-test level of knowledge regarding PCOS among adolescent girls in Selected high schools at Mangalore.2. To evaluate the effectiveness of Planned Teaching Programme on knowledge regarding Polycystic Ovarian Syndrome among adolescent girls in selected high schools at Mangalore.3. To find the association between the pre-test knowledge score of adolescent girls and selected variables.An evaluatory approach with pre-experimental one group pre-test post-test design was used for the study. The subjects were 100 adolescent girls selected by convenience sampling technique. PTP was administered after the assessment of pre-intervention knowledge on PCOS. Post intervention knowledge was assessed on the 7th day of the administration of PTP through the same structured knowledge questionnaire. The results of this study in general showed, the significant difference between the mean pre-test and posttest knowledge score (t99=7.02, p<0.05).The significant difference was found in between all the areas. There was no association between the pre-test knowledge score and selected demographic variables. Hence it can be concluded that PTP was effective in gaining knowledge of adolescent girls on PCOS. which was evident in post-test knowledge score.
Keywords: Knowledge; Effectiveness; Adolescent girls; Planned Teaching Programme (PTP)